FOREIGN DIRECT INVESTMENT IN THE BRICS GROUP DURING THE PERIOD (2011-2021) - Bourekab Nabil; Bellarou Ali; Ghouila Loubna (International Journal of Innovative Technologies in Social Science, 2025)
The BRICS group consists of a set of emerging economies, despite differences in historical backgrounds and development experiences, these countries share the common characteristic of having achieved high levels of economic development and significant economic growth rates over the past two decades, These nations possess key factors that qualify them to hold an important position in global economic relations. Although the BRICS group has officially commenced its operations, it has yet to evolve into a fully-fledged economic bloc. Its activities have so far been limited to cooperation in economic, financial, and other sectors. Until now, the group has not reached an agreement on the most basic forms of economic integration, such as a free trade area or a preferential trade agreement. The BRICS countries are among the largest recipients of foreign direct investment (FDI) globally. Despite the relatively low volume of intra-BRICS FDI, there is potential for its growth in the future, making it a crucial tool for strengthening economic relations among the member states.